Sacubitril/valsartan mitigates cisplatin-induced liver injury through modulation of oxidative stress, Caspase-3 activity, and RXR-α signaling in experimental rats - Alshammari, Majed N.; Alhowail, Ahmad H.; Abdel-Bakky, Mohamed S.; Aldubayan, Maha A. (Frontiers in Pharmacology, 2026)
BackgroundCisplatin (CIS) is a highly effective chemotherapeutic agent widely used to treat solid tumors. However, its clinical use is significantly limited by dose-dependent hepatotoxicity, characterized by hepatocellular injury and apoptosis. Despite extensive research efforts, an effective pharmacological strategy to reduce CIS-induced liver dysfunction remains elusive. Sacubitril/valsartan (VS), an angiotensin receptor–neprilysin inhibitor, has shown cytoprotective and anti-apoptotic effects in various models of organ toxicity. However, its ability to protect against CIS-induced liver damage has not been thoroughly studied. This research aimed to assess the hepatoprotective potential of VS in rat models of cisplatin-induced liver toxicity, focusing on oxidative markers including reactive oxygen species (ROS) and malondialdehyde (MDA), as well as the roles of caspase-3 inhibition and modulation of retinoid X receptor-alpha (RXR-α) in its mechanism.MethodsIn this study, adult male Wistar rats were randomly assigned to four groups: control, VS-treated, cisplatin-treated, and CIS + VS co-treated. Hepatotoxicity was induced by administering cisplatin at 8 mg/kg via intraperitoneal injection, repeated over three cycles. Meanwhile, VS was given orally at 60 mg/kg daily for 10 days. Liver biochemical markers, including ROS, MDA, alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), total protein (TP), albumin (ALB), total bilirubin (TBIL), and lactate dehydrogenase (LDH), were measured using ELISA. Liver tissue was examined histologically with hematoxylin and eosin staining, and the expression of caspase-3 and RXR-α was evaluated through immunofluorescence.ResultsCisplatin administration significantly increased ROS, MDA, ALT, AST, ALP, TBIL, and LDH levels, while decreasing TP and ALB, indicating severe liver dysfunction. Histopathology showed extensive hepatocellular degeneration, necrosis, and inflammation. Co-treatment with VS significantly normalized liver function tests, improved protein levels, and maintained normal liver histology. Additionally, VS markedly reduced caspase-3 immunoreactivity while increasing RXR-α expression compared to CIS alone.ConclusionSacubitril/valsartan appears to protect the liver from cisplatin toxicity, primarily by inhibiting oxidative stress and apoptosis through caspase-3 suppression, and modulating RXR-α signaling. These results provide new insights into the mechanisms involved and suggest that VS may be a promising adjunct therapy to lessen cisplatin-induced hepatotoxicity during chemotherapy.